1993
DOI: 10.1002/etc.5620120616
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and toxicological testing of composted explosives‐contaminated soil

Abstract: Static‐pile and mechanically stirred composts of explosives‐contaminated soil at the Umatilla Army Depot Activity (UMDA, Umatilla, OR) in a field composting optimization study were characterized chemically and toxicologically. The concentrations of extractable explosives (e.g., 2,4,6‐trinitrotoluene) in the composts and their aqueous leachates, the mutagenicity of organic solvent extracts from the composts, and the toxicity of compost aqueous leachates to Ceriodaphnia dubia all decreased considerably with 20 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 8 publications
3
32
0
Order By: Relevance
“…Manure composting is a well-described approach for stabilization of nutrients and reduction of pathogens and odors [15]. In addition, composting has been shown to be effective in reducing relatively persistent organic compounds such as pharmaceuticals and personal care products (PPCPs) [16,17], chlorophenol [18] 2,4,6-trinitrotoluene [19,20], diazinon [21], pyrene and simazine [22], 17␤-estradiol and testosterone [23]. Our recent study has also shown that composting is also an effective treatment for reducing oxytetracycline (OTC) levels in manure [24].…”
Section: Introductionmentioning
confidence: 99%
“…Manure composting is a well-described approach for stabilization of nutrients and reduction of pathogens and odors [15]. In addition, composting has been shown to be effective in reducing relatively persistent organic compounds such as pharmaceuticals and personal care products (PPCPs) [16,17], chlorophenol [18] 2,4,6-trinitrotoluene [19,20], diazinon [21], pyrene and simazine [22], 17␤-estradiol and testosterone [23]. Our recent study has also shown that composting is also an effective treatment for reducing oxytetracycline (OTC) levels in manure [24].…”
Section: Introductionmentioning
confidence: 99%
“…The potentially hazardous environmental effects of TNT and its metabolites have been studied using pure compounds in solution and in spiked soils, as well as in soils taken from contaminated sites containing a mixture of these substances (Smock et al, 1976;Parmelee et al, 1993;Simini et al, 1995;Griest et al, 1993Griest et al, , 1995Thiboutot et al, 1997). In fact, certain ammunition production plants and Army installations can often contain TNT, a variety of TNT metabolites (including diamino-nitrotoluenes and monoamino-nitrotoluenes), other nitroaromatics (such as 2,4dinitrotoluene, DNT; 2-amino-6-nitrotoluene, 2A-6NT; 2amino-4-nitrotoluene, 2A-4NT; 1,3,5-trinitrobenzene, TNB), and nitroheterocyclics such as RDX (1,3,5-trinitro-1,3,5-triazacyclohexane) and HMX (1,3,5,7-tetranitro-1,3,5,7-tetrazacyclo-octane), as well as other environmental contaminants such as heavy metals (Griest et al, 1993;Simini et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…C ONTAMINATION OF SOIL and groundwater by munitions wastes and energetic compounds are of environmental concern due to the toxicity exhibited by compounds such as 2,4-dinitrotoluene (2,4-DNT) (Griest et al, 1993;Simini et al, 1995). Surface and subsurface soils have been contaminated with releases from munitions manufacturing facilities (e.g., munitions wastewaters), spills, and military field operations (Pennington and Patrick, 1990;Haderlein et al, 1996;Hundal et al, 1997;Sheramata et al, 1999).…”
Section: Introductionmentioning
confidence: 99%